Effective Diagnosis of Prostate Cancer Based on mRNAs From Urinary Exosomes - Gan, Jiahua; Zeng, Xing; Wang, Xiong; Wu, Ya; Lei, Ping; Wang, Zhihua; Yang, Chunguang; Hu, Zhiquan (Frontiers in Medicine, 2022)
Background: Novel non-invasive biomarkers are urgently required to improve the diagnostic sensitivity and specificity of prostate cancer (PCa). Therefore, the diagnostic value of following candidate genes (ERG, PCA3, ARV7, PSMA, CK19 and EpCAM) were estimated by testing mRNAs from urinary exosomes of patients with primary PCa. Methods: RNAs were extracted from urine exosomes via size-exclusion chromatography (SEC) and analyzed by quantitative reverse transcription-polymerase chain reaction according to manufacturer’s protocol. Results: The expression of urinary exosomal ERG, PCA3, PSMA, CK19 and EpCAM were significantly increased in patients with PCa compared with healthy males. In addition, the levels of urinary exosomal ERG, ARV7, and PSMA were intimately correlated with the Gleason score in PCa patients (P<0.05). The receiver operating characteristic curves (ROCs) showed that urinary exosomal ERG, PCA3, PSMA, CK19 and EpCAM were able to distinguish patients with PCa from healthy individuals with an area under the curve (AUC) of 0.782, 0.783, 0.772, 0.731 and 0.739, respectively. Urinary exosomal PCA3 and PSMA distinguished PCa patients from healthy individuals with an AUC of 0.870. Combination of urinary exosomal PCA3, PSMA with serum PSA and PI-RADS achieved higher AUC compared with PSA alone (0.914 and 0.846, respectively). Kaplan-Meier curves demonstrated that PCA3, ARV7 and EpCAM were associated in androgen-deprivation therapy (ADT) failure time which is defined as from the initiation of ADT in hormone-sensitive stage to the development of castration-resistant prostate cancer. Conclusion: These findings suggested that mRNAs from urinary exosomes have the potential in serving as novel and non-invasive indicators for PCa diagnosis and prediction.